Optimasi Parameter Mesin 3D Bioprinter dengan Response Surface Method - Kartinasari Ayuhikmatin Sekarjati (Teknoin, 2019)
This research uses material polymethylmethacrylate (PMMA) and hydroxyapatite (HA). The composition of PMMA: MMA is 1: 1 with the ratio composition of HA to PMMA powder is 0.50: 1 (w/w). The composition will be printed with a 3D Bioprinter that has 1.5 mm nozzle. The parameters of the 3D Bioprinter`s tested are perimeter speed with a range of 20 mm/s, 30 mm/s and 40 mm/s, infill speed with a range of 50 mm/s, 60 mm/s, and 70 mm/s, and fill density with a range of 40 mm/s, 50 mm/s and 60 mm/s. These parameters were optimized using response surface method with Minitab software 17. The design of specimens to be printed with a 3D Bioprinter machine using ASTM D638 Type 1. This design will be tested with dimensional measurement and tensile strength. The result of this study is indicated the optimal point at 31.15 mm/s for the perimeter speed`s parameter, 58.84 mm/s for the infill speed`s parameter and 64% for the fill density`s parameter. Dimension of the design is added with a scale of 1: 1.02 mm for length`s dimensions, 1: 1.08 mm for width`s dimensions, 1: 1.09 mm for narrow width`s dimensions and 1: 1.17 mm for thick`s dimensions.